Intelligent transport systems exploiting smart wireless sensing nodes - Praticò, Filippo G.; Fedele, Rosario; Pizzi, Sara; Araniti, Giuseppe (International Conference “Environmental Engineering”, 2020)
Future smart cities that will exploit the forthcoming fifth-generation (5G) network will strongly contribute to the development of intelligent transport systems, which will be able to effectively manage changing infrastructural conditions, and to timely exchange crucial information with different stakeholders to improve sustainability and safety. To this end, smart wireless sensing nodes can be effectively exploited. Consequently, the objectives of this study are: 1) to describe the setup and the main potentialities of a wireless sensing system designed for monitoring the environmental and structural conditions on road pavements; 2) to provide an overview about the capability of the 5G network to enable the data exchange required by the designed system. Each sensing node includes different sensors, and is able to send the data gathered from the resource-constrained sensors to a web server used for data processing. Vibrational-, acoustical-, and environmental-related data are used to control traffic pollution, road availability and structural status. The paper describes the in-lab tests carried out on asphalt concrete samples to: i) calibrate the sensors; ii) define structural and environmental thresholds. Results show that the tested node is able to provide reliable data that can be used for the above-described purposes.